1988
DOI: 10.1007/bf01410283
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray diffraction study of alkylammonium humate complexes

Abstract: By exchange of cations of different humates (synthetic, brown coal and compost humates) with an equivalent amount of long-chain organic cations, derivatives with the following alkylammonium ions were prepared: n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl and n-octadecyl ammonium ions. X-ray diffraction of the humic acids and the alkylammonium h umates revealed a behaviour similar to that of smectite-type clay minerals. The results seem to support the layer structure of humic substances. The layers of syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Previous studies performed on surfactant-HA interactions can be found in refs. [12,[20][21][22][23][24][25]. Koopal et al [12] and Adou et al [24] mention that humic acid is removed from the aqueous phase by forming neutral hydrophobic complexes with cationic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed on surfactant-HA interactions can be found in refs. [12,[20][21][22][23][24][25]. Koopal et al [12] and Adou et al [24] mention that humic acid is removed from the aqueous phase by forming neutral hydrophobic complexes with cationic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…In our surfactant-containing system, either homogenous micelles (SDS-SDS, HS-HS) or mixed micelles (SDS-HS) can be formed (Tombácz et al, 1988) due to the solubilization process (Földényi et al, 2013;Senesi, 1993), which is caused here by the anionic surfactant. Mixed micelles are the result of interaction between the hydrophobic moieties of the surfactant and that of HS.…”
Section: Resultsmentioning
confidence: 99%
“…Humic substances (HS) are special and important components of natural organic matter (NOM) present in soil, water, and other geological deposits. Since HS molecules consist of an elongated hydrophobic portion with more anionic (carboxylate) groups, these compounds have amphiphilic character and therefore they can be considered as natural surfactants (Tombácz et al, 1988;Wandruszka, 2000). This character makes them able to form micelles; however, the critical micelle concentration (cmc) of humic acid was estimated to be as high as 10 g l -1 (Tschapek and Wasowski, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies has been performed on surfactant-HA interactions, using alkylammonium-humate complexes by X-ray and interfacial tension measurements (31)(32)(33). Traina et al (34) studied the association of linear alkyl benzene sulphonates with humic substances, which increased with increasing chain length.…”
Section: Introductionmentioning
confidence: 99%